Stability of expanded austenite by gas nitriding process on austenitic stainless steel material under low temperature conditions. (2020) - Deepak, T. Lakshmi; Mithra, G. Ananda; Lokesh, K.; Chandra, B. Sai; Subbiah, Ram
Abstract: Austenitic stainless-steel grade AISI310 are utilized in various applications like heaters, house apparatuses, turbine parts, blower parts. This task researches on the wear conduct of AISI 310 steel treated with gas nitriding treated to various time parameters to 6 h, 12 h and 18 h respectively. Wear test is led by utilizing pin on disc wear testing apparatus contraption for the both nitriding samples and untreated samples to check wear resistance of the material. The wear tests were conducted by applying a constant load of 30 N, constant speed of 500 rpm for a time period of 5 Minutes. Scanning electron microscope perceptions were made for the adjustments in surface and at naturally visible level. Hardness test is performed by utilizing Vickers hardness test and it was found to be improvement in hardness level in treated samples whereas no hardness in untreated samples. The microstructure results demonstrated that a white layer namely expanded austenite that was seen in nitrided samples. Subsequent to nitriding time was expanded, white layer disintegrated to chromium nitride (CrN) stage. From wear results it was noted that huge wear loss was obtained in untreated specimen that leads to expand wear increments. It was seen that hardness increments with the nitriding time. With the wear test and metallographic test outcomes, the best of gas nitrided samples were compared with untreated samples and were contrasted all together with decided to be sample with better wear resistance.